Pemikiran Mbah Buyut Ki Tuan dalam Perkembangan Pendidikan Islam di Desa Karanglo Kecamatan Kerek Kabupaten Tuban - Umam, Hibrul (Indo-MathEdu Intellectuals Journal, 2023)
The background of this problem was the background of the existence of community leaders in Karanglo village and their role in spreading religion to the people who were known laymen at that time. The purpose of this study is to find out the efforts of Mbah Buyut Ki Tuan's thoughts in the development of Islamic education, and how the community maintains the Islamic Education shiar of Mbah Buyut Ki Tuan as a successor in the modernization era. This research uses a qualitative approach type of research whose findings are not obtained through statistical procedures or other forms of calculation and seeks to understand and interpret the meaning of an event of human behavior interaction in certain situations using observation methods, visual analysis, literature study, interviews and the results of the researcher's own thoughts. The results of the study can be concluded that one of the thoughts on the development of Islamic education is different and the problem of the development of thought collects information from several thoughts of resource persons as a problem solver or obstacle in developing Islamic education in Karanglo Village. One of the efforts made by the village kiyai is to develop and maintain the knowledge of syiar mbah Buyut Ki Tuan in Islamic education and increase knowledge of the people of Karanglo village to make and develop the knowledge of ordinary people to be more knowledgeable in Karanglo village